Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.2174/1389450120666190724145937
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Perspective Review on Dengue Research

Abstract: Dengue fever is a disease which is caused by a family of viruses named Flaviviridae which are transmitted by female Aedes mosquitoes. Today, this is endemic in more than 100 nations in the World Health Organization's African, Americas, Eastern Mediterranean, South-East Asia and Western Pacific locales. The treatment of typical dengue is focused on relieving the symptoms and signs. Carica papaya is a very common plant whose leaf extract is used in the treatment of this disease. Despite extensive resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…DENV infectious clones have contributed greatly to antiviral studies, such as screening of compound libraries and determining antiviral mechanisms of candidate compounds. Studies have discovered a number of natural compounds with activity against DENV ( 33 , 34 ), which could constitute candidates for future anti-dengue drug discovery. Previously, we found that patentiflorin A and justiprocumin B, arylnaphthalene lignans extracted from Justicia gendarussa , exhibited activity against HIV ( 35 , 36 ).…”
Section: Introductionmentioning
confidence: 99%
“…DENV infectious clones have contributed greatly to antiviral studies, such as screening of compound libraries and determining antiviral mechanisms of candidate compounds. Studies have discovered a number of natural compounds with activity against DENV ( 33 , 34 ), which could constitute candidates for future anti-dengue drug discovery. Previously, we found that patentiflorin A and justiprocumin B, arylnaphthalene lignans extracted from Justicia gendarussa , exhibited activity against HIV ( 35 , 36 ).…”
Section: Introductionmentioning
confidence: 99%